Dystopia as the Spirit of Our Times: Crisis of Modernity and the Utopian Imaginary; [la Distopía Como Espíritu de Nuestra Época: Crisis de la Modernidad y del Imaginario Utópico] - Retamal-Hernandez, C (Universidad EAFIT, 2024)
This article analyzes how the contemporary dystopian imaginary expresses a profound crisis of the Enlightenment ideals of modernity. Dystopia, as a representation of oppressive societies, concentrates various widespread social fears that question the promises of emancipation of modernity. Originally, modernity was based on utopian conceptions and the notion of progress as a historical driving force. But the internal contradictions of modernity eroded the utopian imagination. In its place arose dystopian imaginaries that globalized anxieties about totalitarianism, the ecological crisis, the loss of individuality, etc. The pandemic and the daily experience of climate change intensified the feeling of imminent catastrophe. The article examines the social and philosophical problems implied in the current preeminence of dystopia. It addresses issues such as uncertainty, existential anxiety, the questioning of identity, and the emergence of new nihilisms. It analyzes the expression of dystopia in mass culture, its political manifestations, and its impact on the vision of the future. Likewise, it explores philosophical problems such as the crisis of the notion of progress, the breakdown of historical teleology, and the extension of left-wing melancholy. Overall, this analysis aims to elucidate how dystopia erodes the emancipatory ideals of the Enlightenment project of modernity. Despite this, it analyzes how dystopia contains a weak inverted utopianism waiting to be developed. © 2024 Universidad EAFIT. All rights reserved.